Comparison of the Chaetodontidae Mitochondrial Genome - Ferdyan, Rhavy; Razak, Abdul; Ahda, Yuni (Biota, 2021)
The mitochondrial genome is useful for identification because the mutation rate of mtDNA is higher than nDNA. Previous studies have carried out many analyses on the mitochondrial genome of several species, the Chaetodontidae group. Fish in this group are biological indicator fish of coral reefs, so their molecular characteristics must be enriched to conserve these fish. This article aims to review several forms of the mitochondrial genome of the Chaetodontidae group of species, including: Chaetodon speculum, Chaetodon octofasciatus, Chaetodon wiebeli, and Heniochus chrysostomus. Data were collected qualitatively by reviewing previous research articles related to the Chaetodontidae mitochondrial genome. The review focused on the characteristics of each species' mitochondrial genome, including length, overall composition, tRNA, and non-coding region. Each species exhibits various features of the mitochondrial genome and is mapped in its phylogenetic analysis.